A Role of Complementary Medicine in Rehabilitation of Military Traumatic Brain Injuries (Medicina bolu, 2018)
Background: Military service members and veterans face health issues related to traumat-ic brain injury (TBI), especially during combat, use of heavy equipment, and exposures to environmental hazards and explosives. There were 1.000 TBIs reported in deployed Ukra-nian troops during Russian-Ukranian war in 2014–2017. Studies have indicated that some manual therapies could be helpful for treating patients who have post-concussive syndrome.Objective: This case series report de-scribes the effects of CranioSacral Therapy (CST), Visceral Manipulation (VM), and Neu-ro-muscular Manipulation (NM) modalities for treating patients who have post-concussion syndrome. The goal of this study was to evalu-ate these effects on immobility, pain intensity, quality of life, sleep disorders, and cognition in these patients.Materials and Methods: This single-blind-ed case series was conducted at the Volunteer rehabilitation center, Dnipro, Ukraine. The pa-tients were 45 male participationers of Ukra-nian military forces who had been medically diagnosed with post-concussion syndrome. Each participant received a morning and af-ternoon 1-hour session of these three spe-cific manual therapies, which were capable of accessing and addressing the structural, vascular, and neuro-muscular tissues of the Cranium, Neck, Diafragm, Peritoneal bag and brain-as well addressing far-reaching ramifi-cations throughout the body following trauma. The main outcome measures were scores on the: Impact Neurocognitive Test; Blood Oxigen Saturation Test; Short Form-36 Quality of Life Survey, Headache Impact Test, a numeric pain rating scale; orthopedic range of motion tests (ROM); and vestibular testing. Hours of sleep were also checked. These outcome measures were registered at baseline, after treatment, and after a 3–6-month follow up.Results: Statistically significant differenc-es were seen with a decrease in overall pain rating scale scores (P = 0.034), and cranio-cer-vicogenic pain levels decreased (P = 0.047). There were statistically significant increases of blood oxigen saturation (P = 0.033), Mem-ory Test (P = 0.017) scores, and cervical ROM scores (P = 0.036). Hours of sleep averaged 1 hours on the first day of treatment and in-creased to 2.0 hours at the end of treatment. Results were continuing to increase, as noted at a 5-month evaluation.Conclusions: Six sessions of specific CST/VM/NM therapy resulted in statistically great-er improvements in pain intensity, ROM, mem-ory, cognition, blood oxigen saturation and breathing in concussed patients.